Agus Syam STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PRODUK DI PT MELIA SEHAT SEJAHTERA CABANG MAKASSAR - Marwah Marwah; Agus Syam; Muhammad Alfa Sikar (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This research aims to analyze the digital marketing strategies in the business development of Melia Sehat Sejahtera (MSS) by examining five key aspects: digital promotion, competitive pricing, brand image strengthening, product innovation, and network empowerment based on the MLM/binary system. This study employs a qualitative approach with a case study method conducted through observation, in-depth interviews, and documentation. The findings reveal that MSS successfully optimizes digital media as an effective communication and promotional tool to expand consumer reach and enhance brand awareness. The competitive pricing strategy (member price) also strengthens loyalty and encourages network growth among members. Brand image reinforcement is carried out through product education, health seminars, and digital content that foster public trust. In addition, natural-based product innovation and differentiated marketing systems increase the company’s competitiveness. Network empowerment through training, mentoring, and incentive systems effectively supports the economic independence of its members. Overall, MSS's digital marketing strategy is holistic and capable of supporting business growth in the digital 4.0 era toward Society 5.0.